Efeitos da ativina A, inibina A e folistatina Sobre células endometriais em um modelo de adesão e invasão peritoneal in vitro. - Marcia Cristina Franca Ferreira Silva (2007)
Objective: The aim of this study was to investigate whether activin A has an effect in the attachment and invasion of endometrial cells in a modeled peritoneum in vitro.Methods: Cultured endometrial stromal and epithelial cells were treated with activin A (concentration range 6.25 to 50 ng/ml) and with activin A 25 ng/ml alone or associated to inhibin A or follistatin. Cells were labeled fluorescent green and added to a monolayer of confluent LP-9 mesothelial cells in a Matrigel® invasion assay. The expression of cell adhesion proteins N-cadherin and E-cadherin was evaluated by Real Time PCR.Results: Activin A (25 ng/ml) promoted an increase in invasion of the endometrial cells through the modeled peritoneum (211 ± 36 percent of control levels, p<0.05), and this effect was partially reversed by its natural antagonists inhibin A and follistatin. Activin A had no effect in the attachment of the endometrial cells to the mesothelial cells or in the in vitro proliferation of endometrial cells. In addition, activin A induced a decreased mRNA expression of E-cadherin in cultured endometrial epithelial cells ( p<0.05).Conclusion: Activin A increases invasion of endometrial epithelial cells and endometrial stromal cells into modeled human peritoneum, and this effect may be at least in part related to down-regulation of E-cadherin expression in endometrial epithelial cells. These findings suggest that activin A is able to facilitate the process by which endometrial cells invade the peritoneum to form endometriotic implants.